KARAKTERISTIK PENGUNJUNG PADA WISATA ALAM AIR TERJUN BATU PUTU KOTA BANDAR LAMPUNG - Refki Eka Putra; Slamet Budi Yuwono; Susni Herwanti; Christine Wulandari (Jurnal Belantara, 2023)
Visitor characteristics are essential in tourism development because they serve as the basis for decision making of the tour management. The purpose of this research is to identify the visitors characteristics on Natural Tourism of Batu Putu. The data were collected through interview method, online questionnaire,Â  and literature study. Then, the data obtained were analyzed descriptive qualitative. The results showed that the visitors characteristics were dominated by the age of 17-25 years with the male gender whose job as an entrepreneur / self-employed and senior high school graduates. The majority of visitors who come have an income of less than Rp. 1000,000. The distance to travel at the location is 5-20 km within less than 1 hour travel. The road is accessible, but the visitorsâ€™ frequency is once visitation.